Use of fluoropolymers as release films in composite molding processes - Patents.com
Patent Information
- Application Number
- JP2023565312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-23
- Filing Date
- 2022-04-21
- Publication Date
- 2025-04-01
AI Technical Summary
Current methods for manufacturing fiber-reinforced polymer composites face challenges such as time-consuming processes, part-to-part variations, and defects like wrinkles and orange peel, which are not adequately addressed by existing film technologies, particularly in high-temperature applications.
The use of single-layer fluoropolymer films, specifically ETFE and PTFE, in a double diaphragm mechanical thermoforming process that allows for high-temperature curing (120-200°C) and self-peeling, ensuring no film failure or contamination, thereby improving part appearance and reducing process time.
The fluoropolymer films enable rapid, reliable production of complex three-dimensional composite structures with improved surface quality, reduced process time, and ease of recycling, suitable for automotive and aerospace applications.
Abstract
Description
Summary of the Invention
[0001] Fiber reinforced polymer composites are widely used in many industries (including aerospace, automotive, marine, industrial, construction, and a variety of consumer products) and are often preferred because they are lightweight while still exhibiting high strength and corrosion resistance, especially in harsh environments. Fiber reinforced polymer composites are typically manufactured either from pre-impregnated materials or from a resin infusion process.
[0002] Pre-impregnated materials, or "prepregs", generally refer to fibers (such as carbon fibers) that have been impregnated with a curable matrix resin (such as epoxy). The resin content in prepregs is relatively high, typically 40% to 65% by volume. Multiple plies of prepregs can be cut to size for lamination and then subsequently assembled and molded in a molding tool. If the prepreg cannot be easily conformed to the shape of the molding tool, heat may be applied to the prepreg to gradually deform it to the shape of the molding surface. Fiber-reinforced polymer composites can also be produced by liquid molding processes, including resin infusion techniques. In a typical resin infusion process, dry fibers bound with a binder are placed in a mold as a preform, and then liquid matrix resin is directly injected (or infused) in situ. After injection (or infusion), the resin-infused preform is cured to obtain the finished composite article.
[0003] For both types of materials, the process of three-dimensional shaping (or molding) of the composite material is crucial to the appearance, properties and performance of the final molded product. It is still common to use a hand layup process to mold a preform into a precise shape, which is time-consuming and often results in significant part-to-part variability. Although other, less manual, methods for shaping composite materials exist (such as vacuum forming, which may use pins, robots and / or actuators to help form the part), such methods have their own drawbacks and shortcomings. In addition, such methods are often time-consuming and do not take into account the rheological behavior and curing characteristics of the composite material. Additionally, the products of such processes are still prone to wrinkles and other defects.
[0004] There remains a need to develop faster, improved and more reliable assemblies and processes that take into account potential drawbacks of composite processing such as processing time, part-to-part variability and product contamination. It is also desirable to provide a process that takes into account rheological behavior and curing characteristics, and where possible, maximizes the use of existing equipment (e.g., metal stamps or presses).
[0005] With the aim of addressing the shortcomings and drawbacks of assemblies and other methods known in the art for isolating composite materials from environmental contaminants, as well as providing a molding process that takes into account the rheological behavior and curing characteristics of composite materials and also has the potential to use existing infrastructure and equipment, a method for molding composite materials implementing a double diaphragm mechanical thermoforming process has been successfully developed. This method provides an effective and efficient means for automatically manufacturing complex three-dimensional composite structures. In this way, three-dimensional composite structures can be manufactured rapidly, repeatedly, and on a large scale.
[0006] For example, this is how this double diaphragm forming technology has been rapidly developed and enabled to be utilized for full scale automotive production.
[0007] Composite volumes in the automotive market continue to grow due to the ever-increasing need for lightweighting of different parts. Therefore, original equipment manufacturers (OEMs) are increasingly turning to speed-capable manufacturing techniques such as compression molding to meet future speed and weight targets.
[0008] However, current solutions often cannot achieve both the required cure temperature range and surface quality of the components, and therefore composite components, especially for visual or Class A applications, require additional rework to meet the standards expected by the automotive industry.
[0009] The method using the double diaphragm mechanical process implements a diaphragm. In this context, the term "diaphragm" refers to any barrier that divides or separates two different physical regions. The term "diaphragm structure" is also used, which refers to an assembly of one or more diaphragms that define an exterior space and an isolated interior space, for example, an area within an enclosed pocket and an area outside the enclosed pocket. In general, the material used to manufacture the diaphragm is not particularly limited and can be, for example, rubber, silicone, plastic, thermoplastic, or similar material, or can include a film selected from a plastic or elastic layer. The diaphragm may be composed of a single material or may include multiple materials arranged, for example, in layers.
[0010] Films used as diaphragms exist and include one or more layers. However, these films may have significant limitations and lower performance that may preclude their use. Among others, these include both limited cure temperature range (<150°C) and achievable surface quality of the components and therefore cure speeds, especially for high volume manufacturing, such as a range of automotive or aerospace applications, and the inability to fully utilize the speed capabilities of some fast-curing epoxy systems due to high temperature cure (<190°C). For example, this may include a given T range of about 150 to about 200°C. 硬化 This can cause the film to melt and / or break during formation of the composite component at room temperature.
[0011] Additionally, certain release layers soften when processed above their melting temperature, increasing the likelihood of print-through and / or orange peel effects on the cured part surface. Some unbalanced multi-layer compositions of films also cause film curl during assembly, limiting process robustness and ease of use.
[0012] Moreover, multilayer films are less user-friendly. In particular, certain existing films with unbalanced multilayer compositions also cause film curl during assembly, limiting process robustness and ease of use. Furthermore, the use of multilayer films limits the possibility of recycling these films, or at least requires more complicated and expensive processes to be set up.
[0013] Therefore, a need remains to have a film that represents the broad temperature range used in high temperature double diaphragm mechanical processes for the formation of structural composite components, allowing both higher temperature part cure (≦200° C.), significantly reduced process takt times, while simultaneously improving part appearance directly from the mold. The result is a reduction in overall part manufacturing cycle time and costs associated with intermittent rework and repair.
[0014] In addition to these requirements, one of the desired properties of these films is the ability to self-peel. However, at high temperatures the films can have the disadvantage of sticking to composite components, which can especially lead to a deteriorated surface finish.
[0015] The present disclosure addresses these shortcomings by providing the use of certain films in methods that employ a double diaphragm mechanical thermoforming process to form composite materials - both individually and collectively.
[0016] The applicant has discovered that the use of a single layer fluoropolymer film selected from ethylene tetrafluoroethylene (ETFE) film and polytetrafluoroethylene (PTFE) film as a release film for high temperature double diaphragm forming (DDF) makes it possible to obtain a complex structured composite component that can be used over a wide temperature range and therefore can be used as a diaphragm. In addition, this fluoropolymer film selected from ETFE film and PTFE film allows both higher temperature part curing, significantly reducing process tact time, while simultaneously improving part appearance from direct casting.
[0017] Furthermore, this fluoropolymer film selected from ETFE and PTFE films has the advantage of being easily self-peelable allowing for no migration and / or contamination from the composite to the film and / or from the film to the composite after curing.
[0018] The present invention therefore relates to the use of a monolayer fluoropolymer film selected from an ETFE film and a PTFE film as a release film in a method for forming a composite material, said method comprising: (a) placing a substantially planar composite material between upper and lower fluoropolymer films by creating a pocket between the films that receives the composite material; (b) bringing the upper and lower fluoropolymer films into intimate contact with the composite material, thereby forming a layered structure, wherein the composite material is held stationary between the upper and lower fluoropolymer films until heat or force is applied to the layered structure; (c) optionally preheating the layered structure in a heating apparatus at a temperature sufficient to either reduce the viscosity of the composite material or to soften the film; (d) placing the layered structure into a press tool including a male mold and a corresponding female mold separated by a gap, the male mold and female mold each independently having a non-planar molding surface; (e) compressing the layered structure between the male and female molds by closing the gap between the male and female molds; and (f) maintaining the male and female molds in a closed position until the viscosity of the layered structure reaches a level sufficient to maintain the molded shape. Includes Regarding use.
[0019] The upper and lower fluoropolymer films can be independently selected from ETFE and PTFE films. For example, in some embodiments, the lower film can be an ETFE film and the upper film can be a PTFE film. Similarly, for example, in some embodiments, the lower film can be a PTFE film and the upper film can be an ETFE film. However, in preferred embodiments, the fluoropolymers used for the upper and lower films are the same, i.e., either ETFE or PTFE films. In some embodiments, ETFE films are used as the upper and lower films. In other embodiments, PTFE films are used as the upper and lower films.
[0020] According to the present invention, the fluoropolymer film selected from ETFE film and PTFE film is self-releasing, i.e., the film can be easily peeled from the final molded composite part and / or the molded assembly can be easily peeled from the tooling. This provides obvious advantages such as reduced tool wear, protection of the tooling, and zero requirement for application of mold encapsulant or release agent between molded parts, reducing contact work and final part cost, and therefore facilitating full-scale composite structure production.
[0021] Typically, the ETFE film used in the present invention contains at least about 99% by weight, particularly at least about 99.5% by weight, of ethylene tetrafluoroethylene. The ETFE film may also contain polymer additives such as heat or processing stabilizers, antistatic agents, lubricants.
[0022] Typically, the PTFE film used in the present invention comprises at least about 99% by weight, particularly at least about 99.5% by weight, of polytetrafluoroethylene. The PTFE film may also contain polymer additives such as thermal or processing stabilizers, antistatic agents, lubricants, etc.
[0023] According to the present invention, a fluoropolymer film selected from ETFE film and PTFE film is used for high temperature double diaphragm forming (DDF) of complex composite structures using a press. This film has a wide curing temperature range, i.e., a curing temperature T of about 120 to about 200°C, particularly about 120 to about 170°C, especially 120 to about 150°C corresponding to the automotive market standard, and about 150 to about 190°C, especially about 160 to about 190°C corresponding to the aerospace and UAM market standard. 硬化 It has the advantage of being usable over a wide range.
[0024] Thus, the fluoropolymer films selected from ETFE and PTFE films used as release films in the present invention exhibit unique properties.
[0025] At a given curing temperature T, inclusive, from about 120 to about 200°C 硬化 Thus, the film can ensure no melting and / or breakage and proper peel performance throughout the formation of the composite component. Thus, in some embodiments, the fluoropolymer film selected from ETFE film and PTFE film has a melting temperature of about 240° C. or higher. In some embodiments, especially ETFE film has a melting temperature of about 240° C. or higher. In some embodiments, especially PFTE film has a melting temperature of about 300° C. or higher.
[0026] In some embodiments, the thickness (t) of the fluoropolymer film selected from ETFE film and PTFE film, depending on the shape of the composite component, ranges from about 10 microns to about 200 microns, in particular from about 20 microns to about 150 microns. Preferably, the film has a thickness of about 30 microns to about 100 microns. In some embodiments, in particular, the thickness (t) of the ETFE film ranges from about 30 microns to about 100 microns, preferably from about 50 microns to about 80 microns. In some embodiments, in particular, the thickness (t) of the PTFE film ranges from about 30 microns to about 100 microns. This thickness makes it possible to obtain the desired mechanical performance of the film and to prevent film wrinkling during preheating and breakage during the formation of the composite component.
[0027] In some embodiments, the fluoropolymer film selected from ETFE film and PTFE film has an elastic modulus (E) of about 300 to about 950 MPa, preferably about 350 to about 900 MPa, and a tensile strength (σ) of about 30 to about 90 MPa, preferably about 35 to about 80 MPa. In some embodiments, the ETFE film, in particular, has an elastic modulus (E) of about 500 to 900 MPa, preferably about 550 to about 800 MPa, and a tensile strength (σ) of about 45 to about 90 MPa, preferably about 50 to about 65 MPa. In some embodiments, the PTFE film, in particular, has an elastic modulus (E) of about 300 to 500 MPa, preferably about 350 to about 450 MPa, and a tensile strength (σ) of about 30 to about 55 MPa, preferably about 35 to about 50 MPa. This can help prevent film breakage during composite component formation.
[0028] Ensuring the desired component shape is achieved at a given T, including from about 120 to about 200°C. 硬化 The films used in the present invention have a specific elongation at break (ε) that can be achieved without film breakage during formation at ambient temperatures T. In some embodiments, the fluoropolymer films selected from ETFE and PTFE films exhibit an elongation at break (ε) in either the machine or transverse direction in the range of about 400 to about 700%, particularly about 450 to about 650%, at a speed of about 8 mm / sec under ambient conditions, where typically 周囲 is about 20 to about 25° C. In some embodiments, particularly, the ETFE film exhibits an elongation at break (ε) in the range of about 400 to about 700%, particularly about 450 to about 600%, in either the machine or transverse direction at a speed of about 8 mm / sec under ambient conditions. In some embodiments, particularly, the PTFE film exhibits an elongation at break (ε) in the range of about 400 to about 700%, particularly about 450 to about 650%, in either the machine or transverse direction at a speed of about 8 mm / sec under ambient conditions.
[0029] Such films have a sufficiently large width so as not to limit the size of the composite components. In some embodiments, the product width of the fluoropolymer film selected from the ETFE film and the PTFE film is about 1.2 m or more. Preferably, the product width is about 1.5 m or more.
[0030] Thus, in a preferred embodiment, the fluoropolymer film used according to the invention, selected from ETFE and PTFE films, - Melting temperature (T 溶融 ), - a thickness (t) ranging from about 10 microns to about 200 microns, in particular from about 20 microns to about 150 microns, more particularly from about 30 microns to about 100 microns; - an elastic modulus (E) ranging from about 300 to about 950 MPa, preferably from about 350 to about 900 MPa; - a tensile strength (σ) ranging from about 30 to about 90 MPa, preferably from about 35 to about 80 MPa, and - elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 650%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions has.
[0031] In another preferred embodiment, the ETFE film used according to the invention is - Melting temperature (T 溶融 ), - a thickness (t) ranging from about 30 microns to about 100 microns, preferably from 50 microns to about 80 microns; - an elastic modulus (E) ranging from about 500 to about 900 MPa, preferably from about 550 to about 800 MPa; - a tensile strength (σ) ranging from about 45 to about 90 MPa, preferably from about 50 to about 65 MPa, and - elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 600%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions has.
[0032] In another preferred embodiment, the PTFE film used according to the present invention is - Melting temperature (T 溶融 ), - a thickness (t) in the range of about 30 microns to about 100 microns, an elastic modulus (E) ranging from about 300 to about 500 MPa, preferably from about 350 to about 450 MPa; - a tensile strength (σ) ranging from about 30 to about 55 MPa, preferably from about 35 to about 50 MPa, and - elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 650%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions has.
[0033] Film thermal properties such as melting temperature can be measured using Differential Scanning Calorimetry (DSC) according to ASTM D3418, for example by using a differential scanning calorimeter such as a TA Instruments Q2000.
[0034] The mechanical properties of the film, such as tensile strength, tensile modulus and elongation at break, can be measured using Thin Film Tensile Strength & Elongation testing according to ASTM D882-09 (ZM45), for example by using a Zwick Z250 testing machine.
[0035] Typically, ETFE and TFE are thermoplastic fluoropolymers that can be obtained by methods known in the art. For example, ETFE can be processed using standard thermoplastic processing methods such as injection molding, compression molding, blow molding, rotational molding, extrusion, and wire coating. Furthermore, for example, ETFE films can be obtained by blow molding or extrusion lamination techniques. In addition, for example, PTFE films can be obtained by casting, die extrusion or skiving. Such methods are known to those skilled in the art.
[0036] According to an embodiment of the present invention, the ETFE film can be recycled and reused in the process for forming a composite material as claimed in the present invention. For example, once a used ETFE film has been peeled off from the final composite material, it can be granulated and then extruded, typically in extruders known in the art, to obtain a new film, which can be used in the process for forming a composite material, especially as described above.
[0037] As used herein, the term "substantially planar" refers to a material having one plane that is significantly larger (e.g., at least 2, 3, 4, or 5 times larger, or more) than the other two planes. In some embodiments, a substantially planar material has a variation in thickness along its largest plane. For example, a composite material may include pad-ups (i.e., a local increase in the amount of plies) or ply drops (i.e., a local decrease in the amount of plies), changes in material, and / or reinforcing materials, such as areas where the composite transitions, for example, to a fabric. In other embodiments, a substantially planar material exhibits minimal thickness variation along an area of the composite material. For example, the term substantially planar may mean that the composite material has an overall thickness variation of no more than ±15% over 90% of the area. In some embodiments, the thickness variation is no more than ±10% over 90% of the area. Substantially planar is not intended to mean a completely flat material, but also includes materials that have slight variations in concave and / or convex surfaces.
[0038] In the context of the present invention, the method of forming a composite material can use either a framed or unframed assembly. In some embodiments, the method includes the use of a framed assembly. The upper and lower films are held together by a structural frame that includes a top frame, a middle frame, and a bottom frame, where: The lower film is held between the bottom frame and the central frame; The upper film is held between a center frame and a top frame.
[0039] In a preferred embodiment, the method includes the use of a framed assembly.
[0040] In certain embodiments, the pocket that contains the composite material is defined by a structural frame that contains the composite material held between the films. In certain embodiments, the substantially planar composite material is placed between the upper and lower films. This creates a pocket between the films that contains the composite material. For example, a lower file having a top and bottom surface can be placed with its bottom surface in contact with the top of the periphery of the bottom frame. The composite material can then be placed on top of the lower film; a central frame can then be placed on top of the lower film, followed by the upper film and finally the top frame in contact with the upper film. This arrangement forms a pocket between the lower and upper films that contains the composite material layer. In some embodiments, the central frame may be omitted. The top, middle (if present) and bottom frames define a periphery that maintains the shape of the fluoropolymer film according to the present invention, for example, by the placement of clamps or other fastening means at predetermined intervals around the periphery. Such top, middle and bottom frames can be manufactured based on the size and shape of the composite material to be molded. Optionally, pre-fabricated structural support frames are known in the art for use with conventional metal or composite press tools (eg, from manufacturers such as Langzauner or Schubert).
[0041] In some embodiments, the central frame may include a means for removing air, such as a vacuum port or other valve. The vacuum port, if present, is connected to a vacuum source (e.g., a vacuum pump). In some embodiments, the pocket that contains the composite may be an enclosed pocket, such as an airtight enclosed pocket, whereby the structural frame is disposed around the entire perimeter of the composite material and prevents air or contaminants from entering the pocket.
[0042] The upper and lower films are brought into intimate contact with the composite material to form a layered structure. This can be accomplished, for example, by applying a vacuum pressure between the upper and lower films. In other embodiments, this can be accomplished by physically applying pressure (e.g., manually or by mechanical means) to the upper and / or lower films to remove air. Vacuum pressure may be desired in certain cases, for example, to extract most of the residual air that may hinder molding performance, thus minimizing deformation or wrinkling of the composite material (or its components). The vacuum also prevents film wrinkling and adds stability to the overall assembly. The use of vacuum pressure may also help maintain fiber alignment, support the material during processing and molding, and / or maintain a desired thickness at elevated temperatures. The term "vacuum pressure" as used herein refers to a vacuum pressure of less than 1 atmosphere (or less than 1013 mbar). In some embodiments, the vacuum pressure between the films is set to less than about 1 atmosphere, less than about 800 mbar, less than about 700 mbar, or less than about 600 mbar. In some embodiments, the vacuum pressure between the films is set to about 670 mbar. At this point, whether by vacuum or other means, such as mechanical means, the composite material is held firmly between the films such that it remains stationary until heat and / or force is applied. Such a stationary layered structure can be advantageous, for example, because the composite material held within the layered structure is not only maintained stationary in its position with sufficient tension across the X and Y axes, but it is also indexed. That is, the composite material may be placed (e.g., by automated means) in a specific position between the films within the stationary layered structure. This indexed stationary layered structure may then be placed (e.g., by automated means) in a specific position (as described in more detail herein below) on a press tool such that the press tool consistently engages a predetermined area of the composite material. The stationary layered structure may therefore be reliably used to manufacture multiple copies of a molded product without the need to index each composite blank individually.
[0043] In some embodiments, the composite material can be machined according to the pattern prior to step (a).
[0044] The layered structure may be preheated in a heating device in some cases. The layered structure may be placed in the heating device manually or by automated means, for example, using an automated shuttle. The heating device may be any heater that can be used in forming or shaping metal or composite products, for example, contact heaters or non-contact heaters (i.e., ceramic heaters or infrared (IR) heaters). In some cases, this preheating softens the upper and lower films, for example, so that they are more flexible during the formation of the final molded product. In some cases, this preheating brings the composite material held within the layered structure to a desired viscosity or temperature to allow complex shapes to be formed from a flat initial layup. Preheating may occur in a heating device heated to a temperature above about 75°C, 100°C, 125°C, 150°C, 175°C, 190°C. This temperature may be adjusted, for example, depending on the identity of the components in the composite material. Such pre-heating can be advantageous, for example, when it is desired to minimize heating of the press tool and / or to minimize the amount of time the layered structure is within the press tool.
[0045] To form the final molded product, the layered structure is placed into a press tool. In some embodiments, no vacuum pressure is applied to any part of the press tool. In other embodiments, a localized vacuum is applied to the tool surface, for example to remove air trapped between the layered structure and the tool. However, in such embodiments, the vacuum is typically not used as a force to form the shape of the final molded product. The layered structure can be placed into the press tool manually or by automated means, for example, using an automated shuttle. The press tool generally includes a male and a female mold, separated by a gap. Each mold has a non-planar molding surface. In some embodiments, a mold release agent can be added to the male mold, the female mold, or both. Such a mold release agent can be useful, for example, to remove the molded part from the mold while it is still at a temperature above ambient temperature. In some embodiments, a mold release agent is not required. The mold surfaces are fixed, i.e., not reconfigurable. The mold surfaces are also typically matched, i.e., the male mold is approximately the inverse of the female mold; in some embodiments, they can be perfectly matched. However, in some embodiments, the male and female molds are such that when closed, there is a varying thickness between them, in certain embodiments, the layered structure is disposed in the gap at a specific, predetermined distance between the male and female molds.
[0046] The layered structure is then compressed between the male and female molds by closing the gap between the molds (step (e)). In some embodiments, this is achieved by partially closing the gap between the male and female molds to form a smaller gap between the molds. This smaller gap is then closed after a certain time or viscosity is reached. "Closing the gap" is understood to refer to compressing the molds such that a predetermined final cavity thickness along the Z axis is obtained between the molds. The final cavity thickness can be adjusted, for example, by controlling where the molds stop relative to each other, the choice of thickness can be made by the mold operator and will depend on the nature of the final molded product. In some embodiments, the final cavity thickness is substantially uniform, i.e., the process produces a two-sided molded final product whose thickness varies by less than 5%. In some embodiments, the process produces a final molded product with a thickness that varies by less than about 4%, for example, less than about 3%, less than about 2% or even less than about 1%. In other embodiments, the male and female tools may be arranged to provide cavity thicknesses that vary purposefully across the X and Y axes.
[0047] In certain embodiments, the male and female molds are maintained at a temperature above ambient temperature. For example, they may be maintained at a temperature above about 75°C, 100°C, 125°C, 150°C, 175°C, 200°C or even higher, particularly at a temperature of, for example, about 120 to about 200°C. This temperature can be adjusted depending on the identity (as well as the viscosity and reactivity) of the components in the composite. The mold can be maintained at a temperature above the softening point of the binder or matrix material used in the composite, for example. In some embodiments, the composite comprises a thermosetting material and the mold is maintained at a temperature of about 100°C to 200°C. The binder or matrix material in the composite is in a solid phase at ambient temperature (20°C to 25°C) but will soften when heated. This softening allows for molding of the composite in a press tool and conformation of the flat preform to the final component shape.
[0048] In some embodiments, the male and female molds are maintained in a closed position for a predetermined time to form a molded structure. For example, in some embodiments, the mold is heated and maintained in a closed position until a desired viscosity or temperature is reached. In some embodiments, the mold is heated until the viscosity of the composite material reaches about 1.0×10 8 The mold is maintained in the closed position until the composite material has a viscosity of less than about 1000 psi. In some embodiments, the mold is heated and maintained in the closed position until the binder or matrix material begins to crosslink. In other embodiments, the mold is not heated but is maintained in the closed position for a time sufficient for the material to maintain its molded shape. The mold may be maintained in the closed position for from 1 minute to about 60 minutes, such as from about 5 minutes to about 20 minutes, or such as from about 1 minute to about 10 minutes. The length of time the mold is maintained in the closed position will depend on many factors, such as the identity of the composite material and the temperature of the mold.
[0049] In certain embodiments, the male mold is moved through the layered structure while the female mold remains stationary. In other certain embodiments, the female mold is moved through the layered structure while the male mold remains stationary. In other embodiments, the female mold does not remain stationary but moves at a slower speed than the male mold (so that the male mold still functions primarily as a forming surface). In still other embodiments, both molds move at about the same speed to close the gap between the molds. The molds are moved at a speed sufficient to deform / mold the composite material into the desired shape and to a final pressure. For example, the molds may be moved at a speed of about 0.4 mm / s to about 500 mm / s, such as about 0.7 mm / s to about 400 mm / s, especially about 1 mm / s to about 350 mm / s, such as 5 mm / s to 350 mm / s or about 50 mm / s to 300 mm / s. Moreover, the mold may be moved to a final pressure of about 30 psi to about 1000 psi, particularly about 100 psi to about 800 psi, or about 250 psi to about 750 psi. In some embodiments, the mold is moved at a speed and to a final pressure selected to control the thickness of the final molded product while avoiding the formation of wrinkles and distortion of the structural fibers. In addition, the mold may be moved at a speed and to a final pressure selected to allow for rapid formation of the final molded part.
[0050] The gap between the male and female molds is then opened. The molded structure may be cooled below the glass transition temperature of the binder or matrix material while it remains on the press tool. However, in some embodiments, the molded structure is removed from the press tool before it is cooled below the glass transition temperature of the binder or matrix material. All molded structures are more easily removed from the press tool thanks to the use of the fluoropolymer release film of the present invention. When the binder or matrix material cools below its glass transition temperature, it returns to a solid phase and the composite retains its newly formed shape. If the composite is a preform, such a preform will retain its desired shape for subsequent resin infusion.
[0051] Once the molded structure is obtained, the clips and / or fasteners are released and the different frames are removed from the film. The film and cured composite part are then removed and the film is peeled away from the cured composite component.
[0052] According to the present invention, the fluoropolymer film selected from ETFE film and PTFE film is self-peeling.Thus, the film can then be easily peeled off the final molded part to obtain a good display surface finish of the cured composite part after curing without any sign of surface porosity or weave distortion, while simultaneously limiting as much of the fabric print-through and orange peel effect as reasonably practical.
[0053] Additionally, if necessary, the film can be temporarily maintained on the final molded product, for example, a temporary film may be desirable to protect the component from environmental contamination, e.g., contamination, prior to further processing, i.e., finishing / painting.
[0054] As used herein, the term "composite material" refers to an assembly of structural fibers and binder or matrix materials. The structural fibers may be organic fibers, inorganic fibers, or mixtures thereof, including, for example, commercially available structural fibers such as carbon fibers, glass fibers, aramid fibers (e.g., Kevlar), high modulus polyethylene (PE) fibers, polyester fibers, poly-p-phenylene-benzobisoxazole (PBO) fibers, quartz fibers, alumina fibers, zirconia fibers, silicon carbide fibers, other ceramic fibers, basalt, natural fibers, and mixtures thereof. It is noted that end applications requiring high strength composite structures will typically employ fibers with high tensile strength (e.g., ≧3500 MPa or ≧500 ksi). Such structural fibers may include one or more layers of fibrous materials in any conventional configuration, such as, for example, unidirectional tape (unitape) webs, nonwoven mats or veils, woven fabrics, knitted fabrics, non-crimped fabrics, fiber tows, and combinations thereof. It should be understood that the structural fibers may be included as one or more plies throughout all or a portion of the composite, or in the form of pad-ups or ply drops, with localized increases / decreases in thickness.
[0055] The fibrous material is held in place and stabilized by a binder or matrix material such that the alignment of the fibrous material is maintained and the stabilized material can be stored, transported and handled (e.g., molded or otherwise deformed) without fraying, unraveling, tearing, buckling, wrinkling or otherwise reducing the integrity of the fibrous material. Fibrous materials held by small amounts (e.g., typically less than about 10% by weight) of binder are typically referred to as fibrous preforms. Such preforms would be suitable for resin infusion applications, such as RTM. Fibrous materials may also be held by large amounts of matrix material (commonly referred to as "prepregs" when referring to fibers impregnated with a matrix) and thus would be suitable for final product formation without further addition of resin. In certain embodiments, the binder or matrix material is present in the composite material in an amount of at least about 30%, at least about 45%, at least about 40%, or at least about 45%.
[0056] The binder or matrix material is generally selected from thermoplastic polymers, thermosetting resins, and combinations thereof. When used to form a preform, such thermoplastic polymers and thermosetting resins may be introduced in a variety of forms, such as powders, sprays, liquids, pastes, films, fibers, and nonwoven veils. Means of utilizing these various forms are generally known in the art.
[0057] Thermoplastic materials include, for example, polyesters, polyamides, polyimides, polycarbonates, poly(methyl methacrylate), polyaromatics, polyesteramides, polyamideimides, polyetherimides, polyaramids, polyarylates, polyaryletherketones, polyetheretherketones, polyetherketoneketones, polyacrylates, poly(ester)carbonates, poly(methyl methacrylate / butyl acrylate), polysulfones, polyarylsulfones, copolymers thereof, and combinations thereof. In some embodiments, the thermoplastic material may also include one or more reactive end groups, such as amine or hydroxyl groups, that react with epoxides or curing agents.
[0058] Thermosetting materials include, for example, epoxy resins, bismaleimide resins, formaldehyde condensation resins (including formaldehyde-phenolic resins), cyanate resins, isocyanate resins, phenolic resins, and mixtures thereof. The epoxy resins may be mono- or polyglycidyl derivatives of one or more compounds selected from the group consisting of aromatic diamines, aromatic monoprimary amines, aminophenols, polyhydric phenols, polyhydric alcohols, and polycarboxylic acids. The epoxy resins may be multifunctional (e.g., difunctional, trifunctional, and tetrafunctional epoxies).
[0059] In some embodiments, combinations of thermoplastic polymers and thermosets are used in composites. For example, certain combinations may work in synergy with respect to flow control and flexibility. In such combinations, the thermoplastic polymer provides flow control and flexibility to the blend and will typically dominate over the low viscosity, brittle thermoset.
[0060] The use of the particular fluoropolymer film described above not only aids in the shaping of the composite material, for example by maintaining the composite material in a fixed position with sufficient tension across its X and Y axes, but also provides important additional functional benefits. For example, this arrangement protects the composite material blank from environmental contaminants, such as impurities in the air or on the tooling machine. This protection allows the use of conventional press tools (otherwise cumbersome) for the processing of two-dimensional preforms into three-dimensional complex shapes, thus allowing significantly more complex three-dimensional shapes than either vacuum forming or reconfigurable tooling techniques. Furthermore, the use of a double diaphragm arrangement can allow the demolding process to be eliminated from the overall process.
[0061] The double diaphragm mechanical thermoforming process described herein therefore provides an effective and efficient means of automatically producing complex three-dimensional composite structures from two-dimensional flat preforms for both automotive, UAM and aerospace markets. Three-dimensional composite structures can be produced rapidly, repeatedly, and at large scale. For example, three-dimensional composite structures can be formed from substantially planar composite blanks in 1-10 minute cycles, or in 5-20 minute, or 10-30 minute cycles, or in 20-60 minute cycles, depending on the identity of the desired part and composite material. Such rapid, repeatable processes are suitable for the production of automotive parts and panels, such as hoods, trunks, door panels, fenders, and wheel wells. EXAMPLES
[0062] The following examples are for illustrative purposes only and should not be construed as limiting the scope of the appended claims.
[0063] Example 1: Double-Diaphragm Mechanical Thermoforming with Frame Using High-Temperature ETFE Film and Fast-Cure Automotive Epoxy Prepreg A lower flexible diaphragm made of 52 micron ETFE film was placed onto the base plate holding the bottom frame. This film exhibits the characteristics reported in Table 1.
[0064] [Table 1]
[0065] A composite blank made of carbon fiber reinforced epoxy (Solvay, formerly Cytec Industries, MTM58B) and a surface film (Solvay, formerly Cytec Industries, VTF266) was placed on top of the lower flexible diaphragm, followed by a central frame with a vacuum port. An upper flexible diaphragm made of the same film as the lower flexible diaphragm was then placed so that it covered the central frame and the composite blank. The top, central and bottom frames were fastened together, thereby creating a vacuum tight seal and an enclosed pocket surrounded by the lower flexible diaphragm, the upper flexible diaphragm and the central frame. A vacuum was then pulled until a vacuum pressure of up to 670 mbar was reached, removing the air from between the upper and lower flexible diaphragms. At that point, the composite blank was firmly supported by both diaphragms, creating a layered structure that was immobile.
[0066] The layered structure was then shuttled into a non-contact heating device where it was heated to 140°C. As soon as the outer film temperature reached a maximum of 120°C, it was shuttled into a press tool containing matched male and female dies configured in the shape of a structural automotive Class A demonstrator component. The female die was then moved towards the male die at a speed of approximately 4 mm / sec (250 mm / sec). The female die was kept stationary and both dies were held at 150°C until crosslinking began. The molded structure was removed from the press tool while still hot and allowed to cool after removal. The process of molding the composite blank was 15 minutes from start to finish (i.e., from initial placement of the lower flexible diaphragm to establishment of the final shape).
[0067] After demolding and cooling, parts produced using the 52 micron ETFE top film were visually inspected and scanned using shortwave and longwave scanning techniques (Visuol) to confirm the levels of orange peel (fine) and fabric print-through (coarse), respectively. The results show that the improved thermal performance and film stiffness of the ETFE top film enabled a significant reduction in the measured print-through and orange peel.
[0068] The thermal properties of the films were measured using Differential Scanning Calorimetry (DSC) using a TA Q2000 DSC machine per ASTM 3418. A heat / cool / heat procedure was applied, screening the temperature range from -30°C to 300°C with cooling and heating rates of 10°C / min.
[0069] The mechanical properties of the films were measured according to ASTM D882-09 using a Zwick Z250 testing machine. The films were tested in both the machine and cross directions at a test speed of about 8 mm / sec (500 mm / min) under ambient conditions of 23° C. and 50% relative humidity.
Claims
1. 1. Use of a monolayer fluoropolymer film selected from ethylene tetrafluoroethylene and polytetrafluoroethylene films as a release film in a method for forming a composite material, the method comprising: (a) placing a substantially planar composite material between an upper fluoropolymer film and a lower fluoropolymer film by creating a pocket between the upper and lower fluoropolymer films for receiving the composite material; (b) bringing said upper fluoropolymer film and said lower fluoropolymer film into intimate contact with said composite material, thereby forming a layered structure, wherein said composite material is held stationary between said upper fluoropolymer film and said lower fluoropolymer film until heat or force is applied to said layered structure; (c) optionally preheating the layered structure in a heating apparatus at a temperature sufficient to either reduce the viscosity of the composite material or to soften the film; (d) placing the layered structure into a press tool including a male mold and a corresponding female mold separated by a gap, the male mold and the female mold each independently having a non-planar molding surface; (e) compressing the layered structure between the male and female molds by closing the gap between the male and female molds; and (f) maintaining the male and female molds in a closed position until the viscosity of the layered structure reaches a level sufficient to maintain the molded shape. Including, use.
2. The fluoropolymer film is - A melting temperature (T 溶融 ), a thickness (t) ranging from about 10 microns to about 200 microns, in particular from about 20 microns to about 150 microns, and more particularly from about 30 microns to about 100 microns; - an elastic modulus (E) ranging from about 300 to about 950 MPa, preferably from about 350 to about 900 MPa; a tensile strength (σ) ranging from about 30 to about 90 MPa, preferably from about 35 to about 80 MPa; and - an elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 650%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions; 2. The use according to claim 1, having the formula:
3. The use according to claim 1 , wherein the upper fluoropolymer film and the lower fluoropolymer film are the same film.
4. The use according to claim 1 , wherein the fluoropolymer film is an ethylene tetrafluoroethylene film.
5. The use according to claim 1 , wherein the fluoropolymer film is a polytetrafluoroethylene film.
6. The ethylene tetrafluoroethylene film is - A melting temperature (T 溶融 ), a thickness (t) ranging from about 30 microns to about 100 microns, preferably from 50 microns to about 80 microns; - an elastic modulus (E) ranging from about 500 to about 900 MPa, preferably from about 550 to about 800 MPa; a tensile strength (σ) ranging from about 45 to about 90 MPa, preferably from about 50 to about 65 MPa; and - an elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 600%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions; 5. The use according to claim 4, having the formula:
7. The polytetrafluoroethylene film is - A melting temperature (T 溶融 ), a thickness (t) ranging from about 30 microns to about 100 microns; - an elastic modulus (E) ranging from about 300 to about 500 MPa, preferably from about 350 to about 450 MPa; a tensile strength (σ) ranging from about 30 to about 55 MPa, preferably from about 35 to about 50 MPa; and - an elongation at break (ε) in the range of about 400 to about 700%, in particular about 450 to about 650%, in either the machine or transverse direction at a speed of about 8 mm / s under ambient conditions; 6. The use according to claim 5, having the formula:
8. 2. The use according to claim 1, wherein step (e) comprises partially closing the gap between the male mould and the female mould such that a smaller gap is formed between the male mould and the female mould, which smaller gap is then closed after a certain time or viscosity is reached.
9. 2. The use according to claim 1, wherein the male mould and the female mould are maintained at a temperature above ambient temperature.
10. 10. The use according to claim 9, wherein the male mould and the female mould are maintained at a temperature above 100°C.
11. 2. The use of claim 1, wherein step (e) comprises closing the gap between the male and female molds at a speed of about 0.7 mm / sec to about 400 mm / sec while maintaining the male and female molds at a temperature above the softening point of the composite material.
12. The upper fluoropolymer film and the lower fluoropolymer film are held together by a structural frame including a top frame, a middle frame and a bottom frame, wherein: the lower fluoropolymer film is held between the bottom frame and the center frame; the upper fluoropolymer film is held between the center frame and the top frame; 2. The use according to claim 1.
13. The use of claim 12, wherein the central frame provides a vacuum source to the assembly.
14. The use of claim 1, wherein the upper fluoropolymer film and the lower fluoropolymer film are held together by a structural frame including a top frame and a bottom frame, and both the lower fluoropolymer film and the upper fluoropolymer film are held between the bottom frame and the top frame.
15. 2. The use according to claim 1, wherein the layered structure is placed into the press tool and into an optional heating device by automated means.
16. 2. The use according to claim 1, wherein the composite material comprises structural fibres of a material selected from aramid, high modulus polyethylene (PE), polyester, poly-p-phenylene-benzobisoxazole (PBO), carbon, glass, quartz, alumina, zirconia, silicon carbide, basalt, natural fibres and combinations thereof.
17. The use according to claim 1 , wherein the composite material comprises a binder or matrix material selected from thermoplastic polymers, thermosetting resins, and combinations thereof.